Kritik Ibnu Al-Munayyir terhadap I’tizaliyyat pada Konsep Iman dan Fasik dalam Tafsir Al-Kasysyaf : (Kajian Analisis Kitab al-Intishaf Karya Ibnu al-Munayyir) - Asep Saepulloh Athaya (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2022)
One of the popular commentary books written in the golden era of Islam is the book Al-Kasysyaf by az-Zamakhsyari (d. 538 H). The full name of this book is Al-Kasysyaf 'an Haqa'iq Ghawamidh at-Tanzil wa 'Uyun al-Aqawil fi Wujuh al-Ta'wil. This book of commentary, in terms of language, the beauty of its literary composition and balaghah, is a book of commentary that is unparalleled. However, as mufassir in general, the discussion and content of interpretation of the Qur'an are always influenced by the religious beliefs and expertise of the mufassir, so it is with az-Zamakhsyari in the book Al-Kasysyaf. His book is influenced by the rationality of Mu'tazilah understanding, so that his interpretation is colored with I'tizaliyyat (elements of Mu'tazilah thought). This paper examines Ibn al-Munayyir's criticism in the book al-Intishaf against I'tizaliyyat which is contained in Al-Kasysyaf's commentary on the concepts of Faith and Wisdom. This research method is qualitative in nature which is descriptive-comparative analysis, namely by explaining the I'tizaliyyat contained in the interpretation of Al-Kasysyaf and analyzing it with the thoughts of Ibn al-Munayyir in the book al-Intishaf, then giving conclusions. The conclusion is according to Ibn al-Munayyir that the I'tizaliyyat contained in al-Kasyaf is an ambiguous understanding and far from the truth.